An Overview on the Personality and Work of Dr Hazim Šabanović (Prilozi za orijentalnu filologiju, 2017)
Dr Hazim Šabanović was one of the most prominent researchers in Ottoman studies of the 20th century, not only in Bosnia and Herzegovina, but also in a wider area. His reputation of a great academic is the result of his grand opus in the field of Ottoman studies. Šabanović’s translations of the Ottoman defters and other archival material testify to that, as do his numerous studies and papers.Apart from some lesser known information from the biography of Hazim Šabanović, this paper presents his creative opus consisting of 186 bibliographical units. It is chronologically divided into four phases, with a short presentation of his orientation and work in each of these phases. In the thematic division, his complete work is classified into four parts: a) Academic and translation work; b) Textbook and books; c) Academic papers, contributions and reviews and d) Encyclopedic entries. The paper gives a short review of these bibliographic units which are prominent in their length, theme and importance for further research, or because they are especially noted for some other peculiarities.The whole life and working journey of this prominent academic was very interesting and dynamic. Šabanović slowly and thoroughly entered this field of science and in time he earned a good reputation in academic circles. He was also equally well respected as a translator – whether he translated defters or other kinds of Ottoman documents, or travelogue literature – in all his translations he showed his knowledge of the translating material by his notes and commentaries. On the other hand, as an author of books in the field of general and cultural history, and also in the field of literary creativity in Oriental languages, as well as the author of numerous other studies, articles and encyclopedic entries, Šabanović always dealt his material superbly.By working at the Institute for Oriental Studies in Sarajevo he contributed to the reputation of this academic institution. When one writes on the opus of Dr Hazim Šabanović, one automatically writes about the Institute for Oriental Studies in Sarajevo. That is the place where the largest number of defters has been translated, as it is also where the academic works of this true erudite and lover of science that he committed whole his life to are.